Nitrogen-doped mesoporous network-like carbon as an efficient metal-free electrocatalyst for oxygen reduction reaction. (28th December 2016) - Guo, Congxiu; Tong, Xili; Guo, Xiang-Yun
Abstract: Nitrogen-doped mesoporous network-like carbon (NMNC) as a high-performance oxygen reduction reaction (ORR) catalyst was synthesized via hydrothermal reaction of glucose solution followed by pyrolysis under ammonia atmosphere. The obtained NMNC sample at 1000 °C (NMNC-1000) exhibits extremely high specific surface area (2588 m 2 g −1 ), large pore volume and mesoporous structure, which facilitates mass transport and exposes more active sites. As a result, NMNC-1000 shows excellent electrocatalytic activity in alkaline media with high half-wave potential (0.759 V vs. RHE) for ORR via a four-electron pathway, which is only 32 mV more negative than that of 20% Pt/C, and stability with noticeable methanol-tolerance and CO anti-poisoning. Graphical abstract: Highlights: Nitrogen-doped mesoporous network-like carbon (NMNC) is synthesized. The NMNC-1000 possesses high BET surface area of 2588 m 2 g −1 and uniform mesopores. The NMNC-1000 exhibits outstanding catalytic activity for ORR in alkaline media. The superior ORR performance origins from nitrogen doping and mesoporous nature.